A Software System for Education at a Distance: Case Study Results - Chesley, Harry; Grudin, Jonathan; Gupta, Anoop; Kimberly, Gregory; Sanocki, Elizabeth; White, Stephen A. (1999)
Computers and networks are increasingly able to support distributed, real-time audio and video presentations. We describe Flatland, a highly flexible, extensible system that provides instructors and students a wide range of interaction capabilities. Prior research focused on the use of such systems for single presentations. We studied the use of Flatland over multi-session training courses. We found that even with prior coaching on the use of the software, instructors and students require experience to understand and exploit the features. Effective design and use will require understanding the evolution of personal and social conventions for these new technologies.